More, Huxley, Eggers, and the Utopian/Dystopian Tradition - Herman, Peter C. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2018)
From its inception in Plato’s Republic and revival in Thomas More’s Utopia, the concept of a perfect (or as More originally put it in a qualification often lost, “best”) form of a republic has been dogged by the spectres of hypocrisy, contradiction, and authoritarianism. However, the matter is more complicated than a simple declaration that utopias provide a vehicle for totalitarian fantasy, that totalitarian governments inevitably portray themselves as creating a utopia. While today’s readers, at a comfortable distance from the early sixteenth century, may bridle at the lack of privacy, or at the ideological coerciveness in More’s Utopia, that does not eradicate how, in Walter Kendrick’s words, “what for us are problems are for them solutions.” It can be argued that the negative elements are a response to social ills. The same goes for Aldous Huxley’s Brave New World and Dave Eggers’s The Circle. While the negatives in all three fictions undermine or put into question the positives, our realization that the authors also intended the negatives as genuine attempts at resolving genuine problems that cause untold misery invites us to complicate our judgments. The undermining is itself undermined.